EXPRESSION OF PALINDROMES IN UZBEK AND ENGLISH - Hikmatullo Do‘smatov, Mohlaroyim Ibrohimova (International Journal of Literature and Language Studies, 2026)
This article provides a comparative-typological analysis of structural, semantic, and linguopoetic features of palindromic units in the Uzbek and English languages. The study explores the mechanisms of palindrome formation and their manifestations at phonetic, lexical, and syntactic levels in both languages. Furthermore, the role of palindromes in artistic speech and poetics, as well as the differences in their manifestation within two distinct language systems (agglutinative and inflectional), are scientifically substantiated.